Fermented table olives from Cyprus: Microbiota profile of three varieties from different regions through metabarcoding sequencing - Kamilari, Eleni; Anagnostopoulos, Dimitrios A.; Tsaltas, Dimitrios (Frontiers in Microbiology, 2023)
The knowledge about the microbial diversity of different olives varieties from diverse regions in the Mediterranean basin is limited. This work aimed to determine the microbial diversity of three different fermented olive varieties, collected from different regions in Cyprus, via Next Generation Sequencing (NGS) analysis. Olives were spontaneously fermented for 120 days, microbial DNA was extracted from the final products, and subjected to 16S rRNA gene and ITS1 loci metabarcoding analysis for the determination of bacterial and fungal communities, respectively. Results revealed that the bacterial profile of the studied varieties was similar, while no noteworthy differences were observed in olives from different regions. The bacterial profile was dominated by the co-existence of Lactobacillus and Streptococcus, while the genera Lactococcus and Salinivibrio and the family Leuconostocaceae were also present in increased relative abundances. Regarding fungal communities, the analysis indicated discrimination among the different varieties, especially in Kalamata ones. The most abundant fungi were mainly the genera Aspergillus, Botryosphaeria, Meyerozyma, and Zygosaccharomyces for Cypriot olives, the genera Botryosphaeria, Saccharomyces, Geosmithia, and Wickeromyces for Kalamata variety, while the dominant fungi in the Picual variety were mainly members of the genera Candida, Penicillium, Saccharomyces, Hanseniospora and Botryosphaeria. Potential microbial biomarkers that distinguish the three varieties are also proposed. Moreover, interaction networks analysis identified interactions among the key taxa of the communities. Overall, the present work provides useful information and sheds light on an understudied field, such as the comparison of microbiota profiles of different varieties from several regions in Cyprus. The study enriches our knowledge and highlights the similarities and the main differences between those aspects, booming in parallel the need for further works on this frontier, in the attempt to determine potentially olives’ microbial terroir in Cyprus. Our work should be used as a benchmark for future works in this direction.